Smoothened-activating lipids drive resistance to CDK4/6 inhibition in Hedgehog-associated medulloblastoma cells and preclinical models - Daggubati, Vikas (J Clin Invest, 2021)
Medulloblastoma is an aggressive pediatric brain tumor that can be driven by misactivation of the Hedgehog (HH) pathway. CDK6 is a critical effector of oncogenic HH signaling, but attempts to target the HH pathway in medulloblastoma have been encumbered by resistance to single-agent molecular therapy. We identified mechanisms of resistance to CDK6 inhibition in HH-associated medulloblastoma by performing orthogonal CRISPR and CRISPR interference screens in medulloblastoma cells treated with a CDK4/6 inhibitor and RNA-Seq of a mouse model of HH-associated medulloblastoma with genetic deletion of Cdk6. Our concordant in vitro and in vivo data revealed that decreased ribosomal protein expression underlies resistance to CDK6 inhibition in HH-associated medulloblastoma, leading to ER stress and activation of the unfolded protein response (UPR). These pathways increased the activity of enzymes producing Smoothened-activating (SMO-activating) sterol lipids that sustained oncogenic HH signaling in medulloblastoma despite cell-cycle attenuation. We consistently demonstrated that concurrent genetic deletion or pharmacological inhibition of CDK6 and HSD11ß2, an enzyme producing SMO-activating lipids, additively blocked cancer growth in multiple mouse genetic models of HH-associated medulloblastoma. Our data reveal what we believe to be a novel pathway of resistance to CDK4/6 inhibition as well as a novel combination therapy to treat the most common malignant brain tumor in children.